Understanding Intra-Species and Inter-Species Prion Conversion and Zoonotic Potential Using Protein Misfolding Cyclic Amplification - Peden, Alexander H.; Suleiman, Suzanne; Barria, Marcelo A. (Frontiers in Aging Neuroscience, 2021)
Prion diseases are fatal neurodegenerative disorders that affect humans and animals that can cross species barriers. A fundamental event in prion disease pathogenesis is the conversion of normal host prion protein (PrPC) to a disease-associated misfolded form (PrPSc). Whether or not an animal prion disease can infect humans cannot be determined a priori. There is a consensus that classical bovine spongiform encephalopathy (C-type BSE) in cattle transmits to humans, and that classical sheep scrapie is of little or no risk to human health. However, the zoonotic potential of more recently identified animal prion diseases, such as atypical scrapie, H-type and L-type BSE and chronic wasting disease (CWD) in cervids, remains an open question. Important components of the zoonotic barrier are (i) physiological differences between humans and the animal in question, (ii) amino acid sequence differences of the animal and human PrPC, and (iii) the animal prion strain, enciphered in the conformation of PrPSc. Historically, the direct inoculation experimental animals has provided essential information on the transmissibility and compatibility of prion strains. More recently, cell-free molecular conversion assays have been used to examine the molecular compatibility on prion replication and zoonotic potential. One such assay is Protein Misfolding Cyclic Amplification (PMCA), in which a small amount of infected tissue homogenate, containing PrPSc, is added as a seed to an excess of normal tissue homogenate containing PrPC, and prion conversion is accelerated by cycles of incubation and ultrasonication. PMCA has been used to measure the molecular feasibility of prion transmission in a range of scenarios using genotypically homologous and heterologous combinations of PrPSc seed and PrPC substrate. Furthermore, this method can be used to speculate on the molecular profile of PrPSc that might arise from a zoonotic transmission. We discuss the experimental approaches that have been used to model the both the intra- and inter-species molecular compatibility of prions, and the factors affecting PrPc to PrPSc conversion and zoonotic potential. We conclude that cell-free prion protein conversion assays, especially PMCA, are useful, rapid and low-cost approaches for elucidating the mechanisms of prion propagation and assessing the risk of animal prions to humans.